Elevated interleukin-10, -22, -24, and -26 in serum samples of children with infectious mononucleosis - Li Dalei; Mao Kangwei; Luo Peiliang; Zheng Ziqiang; Liu Jiangyan; Zhang Chenxi; Gu Siyu; Zhang Rui; Sun Jun; Wang Juan (Journal of Medical Biochemistry)
Background: Infectious mononucleosis (IM) is an infectious disease with different stages of onset, and the pathogenesis of IM remains unclear. This study aimed to investigate the levels of interleukin (IL)-10 family cytokines IL-10, -22, -24, and -26 in serum samples of patients with infectious mononucleosis (IM) and the potential diagnostic values. Methods: Thirty children with IM were enrolled in the study, and serum samples were collected; 30 healthy children served as the controls. Serum samples from the patients and healthy controls were collected, and IL-10, -22, -24, and -26 were determined by the ELISA method. An automatic biochemical analyser detected the serum alanine aminotransferase (ALT) and aspartate aminotransferase (AST). Moreover, potential diagnostic values of IL-10, -22, -24 and -26 have been analysed using ROC curve analysis, and the correlation between the levels of IL-10, -22, -24 and -26 in patients was analysed. Correlation between IL-10, -22, -24, and -26 and ALT and AST were analysed. Results: IL-10, -22, -24, and -26 levels increased in serum samples of patients with IM compared to healthy controls. ROC analysis showed that the AUC of IL-10, -22, -24, and -26 were 0.8500, 0.7078, 0.8056, and 0.9167, respectively, suggesting that IL-10, -22, -24, and -26 were good biomarkers. Moreover, IL-10, -22, -24 and -26 levels were positively correlated with the ALT and AST of the patients. Conclusions: IL-10, -22, -24, and -26 were upregulated in the serum of patients with IM, suggesting they may function as potential biomarkers.